Employee Competence and Job Placement as Determinants of Employee Performance in Local Government: Evidence from the Department of Manpower, Bandung Regency - Dyah Bayu Framesthi; Mira Veranita (Asosiasi Ahli Administrasi Indonesia, 2026)
Employee performance represents a critical organizational capability that supports the effective delivery of public services. Although competence and job placement have been widely recognized as important determinants of performance, their combined influence has received limited attention in local government organizations. This study examines the independent and combined effects of employee competence and job placement on employee performance in the context of a local government agency. The study employed a quantitative explanatory approach using a census of employees. Data were collected through questionnaires, interviews, observations, and document analysis, then analyzed using multiple linear regression after confirming that the data met the required statistical assumptions. The findings show that both employee competence and appropriate job placement have significant positive effects on employee performance. Job placement demonstrates a stronger contribution than competence, while both variables jointly provide substantial explanatory power for variations in employee performance. These findings highlight the importance of aligning employee capabilities with organizational positions to improve performance in the public sector. The study concludes that strengthening competence and implementing merit-based job placement should become complementary human resource management strategies to support more effective and accountable local government performance.